Investigation of the Frozen Bath Layer under Cold Anodes - Donald Picard; Jayson Tessier; Guillaume Gauvin; Donald Ziegler; Houshang Alamdari; Mario Fafard (Metals, 2017)
Hall-Héroult cell stability is highly affected by anode changing operations. Upon the insertion of a cold anode in the cell, a layer of molten cryolite freezes under the anode. The thickness, microstructure, and chemical composition of this layer vary as a function of time and its location in the cell. To better understand the evolution of the frozen layer, mandatory for the validation of numerical models, a measurement campaign was conducted on the anodes having a few hours of operation in the cell. The macrostructure of the selected frozen bath samples has been investigated using computed tomography while scanning electron microscope (SEM) has been used to qualify its microstructure. An energy-dispersive X-ray spectroscope (EDS) coupled to the SEM has revealed the chemical content. The results showed not only very different macrostructures between samples, but also significantly heterogeneous structure within the same sample. Nevertheless, for all samples, there is a clear distinction between the frozen cryolite and alumina/dusting phases, with the latter surrounding the cryolite matrix.